(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to use cluster analysis to classify the countries of the world into homogeneous groups to carry out comparative studies within economic and social research in a way that ensures the correct selection of comparison countries according to an objective scientific basis. The research was conducted to identify homogeneous comparison countries based on the development indicators found on the World Data Bank website (WDB), which number 1,412 indicators for each country, where the number of countries was 196 countries for each year of the study, which extends from 2011 to 2020. The study reached the possibility of conducting a cluster analysis to classify countries into groups. The cluster analysis was conducted and the countries were classified according to the available social and economic indicators. It was found that there are many countries that are homogeneous with Syria according to those indicators, as they were the neighboring countries that could be compared with Syria according to the economic indicators was Iraq and phalastina, and the Arab countries that can be compared with Syria according to economic indicators were: Iraq - Mauritania - Saudi Arabia - Sudan - South Sudan - Yemen - Palestine. Where The BRICS countries that can be compared with Syria according to economic indicators were: Argentina - Ethiopia - Saudi Arabia - South Africa. The neighboring countries that can be compared with Syria according to social indicators were: Iraq - Lebanon - Jordan – Türkiye, and The Arab countries that can be compared with Syria according to social indicators were: Iraq - Jordan - Lebanon - Kuwait - Libya - Morocco - Oman - Qatar - Saudi Arabia - Tunisia -Emirates – Palestine, Where The BRICS countries that can be compared with Syria according to social indicators were: Argentina - Brazil - China - Egypt - India - Iran - Saudi Arabia - South Africa - UAE.